A Subtitling Analysis Of Interrogative Sentence In Snow White And The Huntsman Movie - Sulistyaningsih, Anik, Sigit Haryanto, Drs, M.Hum, Siti Fatimah, SPd, M.Hum (2013)
This research studies the interrogative sentences in subtitling of Snow White and the Hutsman (2012) movie. The objectives of the study are to explain the types of interrogative sentences and to identify the equivalence of interrogative sentences in subtitling of Snow White and the Hutsman (2012) movie. This research applies descriptive qualitative research. The data are in the form of sentences containing interrogative sentences. The researcher uses the subtitle of Snow White and the Hutsman movie as the data source. The collected data are analyzed by using comparing method between English and Indonesian languages. The results of the research show that there are four types of interrogative sentence, namely: Yes-No questions, Alternative interrogatives, WHinterrogatives, and Tag Questions. The researcher has found 130 data of interrogative sentence in subtitling of Snow White and the Hutsman movie. From 130 data, there are 47 or 36,1% data belongs to Yes-No Questions, 5 or 3,8% data belongs to Alternative Interrogatives, 75 or 57,6% data belong to WHInterrogatives, and 3 or 2,3% data belong to Tag Questions. The preceded percentages show that the WH-Interrogatives is the most dominant, it because the speakers in the movie want to get more information. From 130 data, the researcher also finds 125 or 96,1% data belong to the equivalent subtitling and 5 or 3,8% data belong to the non equivalent subtitling. It means that the subtitling in the Snow White and the Hutsman movie is good.